Pengembangan E-Modul Menggunakan Kvisoft Flipbook Mata Pelajaran Dasar-Dasar Kejuruan Teknik Elektronika di SMK Taruna Pekanbaru: Indonesia - Khairul Anshari; Fitri Farida; Febrelly Sabatini (Unit Pelaksana Praktik Kependidikan Terpadu Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Riau, 2024)
The modules used by teachers at SMK Taruna Pekanbaru still do not encourage independent learning interest for students, because the modules used have not been conceptualized in a complete form and the material provided is not fully in accordance with the basic competencies in the curriculum applied at school. The media used still uses blackboard media and lecture methods so that students feel bored and have no motivation to learn. This study aims to produce a Flipbook-based E-Module in the subject of vocational basics of electronic engineering that is valid and practical. The research used the Research and Development method with the 4-D model which was modified into a 3-D model, namely Define, Design and Development. The research subjects were X TE class students of SMK Taruna Pekanbaru. The research instruments were validity questionnaire and practicality questionnaire. The results obtained in the form of E-Module validity data from media experts and material experts with very valid categories and practicality results from teacher and student responses with very practical results.